Implementation of Discovery Based Learning as an Effort to Improve Students' Knowledge About Movement System Health in Humans - Erna Kurniasih (Journal of Islamicate Studies, 2022)
This research dilators behind the problems that were overcome, among others: (1) Students' understanding of the material being taught; especially on Analyzing motion in living things, the human movement system, is still low; (2) The ability of students to solve problems in science learning is not optimal; And (3) active participation of students in learning is still weak.; According to the problem, the effort to fix it is through: (1) Learning improvement activities with Collaborative Classroom Action Research (PTKK) 2 (two) cycles of science subjects; (2) Implementing innovative, creative, effective, and interesting learning by using the DBL (Discovery Based Learning) learning model; And (3) Carry out learning activities Analyzing motion in living things, the human movement system by applying the expository method; question and answer; work in group; observation; discussion The results of CAR activities in science subjects can be stated to be carried out with procedures and activity steps in 2 (two) cycles properly. This is proven, among others: (1) almost all of the students or 86.49% scored above the KKM (72) with an average score (students' Cognitive Mean) of 82.43; (2) Skill level of students according to KD almost entirely or 96.62% of students are skilled in basic competence Analyzing motion in living things, human movement systems with very good qualifications. And (3) the level of active participation of students in learning reached 88.60% which was declared very high.